Abstracts of oral and poster presentations given at the Ascochyta 2012 Workshop, Córdoba, Spain, 22–26 April 2012 - Millan, Teresa (Phytopathologia Mediterranea, 2013)
The third International Ascochyta Workshop was held in Córdoba, Spain 22 - 26 April 2012. This meeting was attended by 70 participants, and 33 oral presentations, 17 posters and 4 invited speeches were presented dealing with Ascochyta blights of the cool season food legumes (peas, lentils, chickpeas and faba beans). In addition, a special session was held on “Food legumes Research in North Africa”. Abstracts of the oral presentations and the posters of the congress are presented in this issue.